Effect of processing route on the phase formation and properties of Bi4Ti3O12 ceramics - Stojanovic, B. D.; Simoes, A. Z.; Paiva-Santos, C. O.; Quinelato, C.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
Our efforts were directed to the preparation of bismuth titanate-Bi4Ti3O12 (BIT) by two procedures: mechanically assisted synthesis and polymeric precursor method to display a variety of their advantages. To follow the nucleation and phase formation of BIT, XRD and Rietveld refinement analysis were used and it was shown that Bi4Ti3O12 ceramic can been successfully prepared from nano-sized powders obtained by both methods. The ferroelectric properties were determined and the loops from BIT obtained by polymeric precursor method were not fully saturated with a remnant polarization of 20 mu C/cm(2) and coercitive field of 1500 kV/cm. BIT obtained from powders prepared by mechanically assisted synthesis shows a remnant polarization of 0.65 mu C/cm(2) and coercitive field of 1050 kV/cm. The grain morphology may be the factor causing the observed differences. (C) 2005 Published by Elsevier Ltd and Techna Group S.r.l.
Keywords: milling; powders : chemical preparation; X-ray methods; electron microscopy; ferroelectric properties; titanates